Growth of the peritrich epibiont Zoothamnium intermedium Precht, 1935 (Ciliophora, Peritrichia) estimated from laboratory experiments - Utz,LRP. (2008)
Peritrich ciliates are commonly found colonizing living substrates. Although this a well known phenomenon, biological aspects of this relationship need to be studied in more detail. Assessment of growth rates in peritrichs has been the subject of very few studies. Only species in the genera Carchesium Ehrenberg, 1830 and Vorticella Linnaeus, 1767 had their growth rates evaluated in the field and in the laboratory. In the present study, growth, colonization (colonies/host), and proliferation (zooids/colony) rates of the peritrich epibiont Zoothamnium intermedium Precht, 1935 attached to the calanoid copepod Acartia tonsa Dana 1848 were evaluated in the laboratory in two food regimes: bacteria only, and algal based diet. Results showed that growth, colonization, and proliferation rates were similar for both diets. Maximum growth rates obtained for Z. intermedium was 0.85 and 0.83 per day, for bacteria and algae respectively. Maximum colonization rates were 0.5 per day for both diets, and the maximum proliferation rates were 0.44 and 0.42 per day for bacteria and algae respectively. These results demonstrate that Z. intermedium is able to grow at the same rate of other peritrichs on bacterial and algal based diets.